The ethical junior: a typology of ethical problems faced by house officers - McDougall, Rosalind (Royal Society of Medicine Press, 2008)
Although many studies have explored the experiences of doctors in their first postgraduate year, few have focused on the ethical issues encountered by this group. Based on an extensive literature review of research involving house officers, we argue that these doctors encounter a broad range of ‘everyday’ ethical challenges, from truth-telling to working in non-ideal conditions. We propose a typology of house officers' ethical issues and advocate prioritizing these issues in undergraduate medical ethics and law curricula.